Facile preparation of a long-term durable nano- and micro-structured polymer blend membrane for a proton exchange membrane fuel cell. Issue 52 (11th May 2016) - Lee, Hye-Jin; Kwon, Yeonhye; Lee, So Young; Choi, Jieun; Kim, Bo Hyun; Henkensmeier, Dirk; Jang, Jong Hyun; Yoo, Sung Jong; Kim, Jin-Young; Kim, Hyoung-Juhn; Kim, Hwayong; Kim, Man-Ho
Abstract : A blend of sulfonated poly(ether sulfone)s with different sulfonation degree (10–40%) shows unique ionic channels in nanoscale and heterogeneity in microscale. Abstract : The blend of sulfonated poly(ether sulfone)s (PESs) with different degrees of sulfonation is used to prepare a membrane for fuel cell applications. Considering their facile preparation and excellent performance, such sulfonated PES blends constitute good candidates as polymer electrolyte for fuel cell applications. The long-term durability of the blend membrane is improved compared to unblended sulfonated polymer membranes with one degree of sulfonation. The nano-to-micron scale morphology of the polymer blend is investigated by transmission electron microscopy. The long-term stability of the blend membrane is related to its morphology, as confirmed by ultra small angle and small angle neutron scattering (USANS and SANS, respectively) analyses. The blend membrane comprises better-defined interconnected nano-sized ionic phases that enhance proton conductivity and water flow and micro heterogeneous domains, which could be reasons for the long-term durability.